Strategi Pembiayaan Pendidikan untuk Penguatan Pendidikan Masyarakat di Indonesia (2020-2025) Kebijakan, Tren Data dan Rekomendasi - Mulyadi, Edi; Solahudin, Mamat; Irfan, Irfan; Imammudin, Muhamad (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Indonesia’s education financing after 2020 has been shaped by three major challenges: the constitutional mandate to allocate at least 20% of the national and regional budgets to education, the transformation of the School Operational Assistance (BOS) into the Education Unit Operational Assistance (BOSP), and the urgency to recover from post-pandemic learning loss while re-engaging out-of-school youth. This study aims to analyze the role of BOSP in supporting non-formal education, particularly Community Learning Centers (PKBM), as a pathway to strengthen civic literacy and expand access for second-chance learners. Employing a policy study approach with secondary data from 2020-2025, the research applied a descriptive-comparative analysis within the policy cycle framework and the input-output-outcome-impact model. The findings indicate that reforms in BOSP such as the integration of BOS and BOP, the age eligibility limit of 7-25 years for equivalency education, and the introduction of digital reporting through ARKAS have enhanced efficiency and accountability. However, persistent challenges remain in addressing the needs of learners over 25 years old, ensuring equitable funding distribution across regions, and consolidating comprehensive PKBM datasets. The study concludes that performance- and context-based unit costs, complementary funding schemes, standardized national PKBM data, and sustained technical assistance are essential to strengthen non-formal education financing in Indonesia.